Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1200/jco.2011.39.4692
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Colorectal Cancer Staging Criteria in TNM Classification

Abstract: The prognostic value of TNM7 is better than that of TNM6; however, improvement over TNM5 is insignificant. By considering all regional NDs as LNM irrespective of their morphology, TNM classification can be simplified and its prognostic value improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 21 publications
0
80
1
1
Order By: Relevance
“…In the present study, we used a C-index calculated on the basis of timedependent ROC curve analysis to quantify the ability to predict survival time in absolute values. There have been reports on scientific, objective C-index-based evaluations of the staging system in terms of the predictive ability for survival outcomes in colorectal cancer and endocrine cell cancer [15,16]; however, no similar reports have been published related to gastric cancer. In the present study, the C-index exceeded 0.7, which is the threshold for moderate predictive ability, even when based on either cT or cN alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we used a C-index calculated on the basis of timedependent ROC curve analysis to quantify the ability to predict survival time in absolute values. There have been reports on scientific, objective C-index-based evaluations of the staging system in terms of the predictive ability for survival outcomes in colorectal cancer and endocrine cell cancer [15,16]; however, no similar reports have been published related to gastric cancer. In the present study, the C-index exceeded 0.7, which is the threshold for moderate predictive ability, even when based on either cT or cN alone.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on objective C-index-based evaluation are available for other cancers [15,16] but not for gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we observed that subdivisions A and B in the stages II and III of the 7th edition do not translate into different prognosis. As a result, the discriminatory indexes were found to be disappointing, similar to those published in colorectal cancer [29]. Recently Sano et al [30] suggested a new staging grouping launched by the International Gastric Cancer Association (IGCA), in which the introduction of pN3a and pN3b subclassification resulted in better stratification especially among stage III subgroups.…”
Section: Os Kiel Protocolmentioning
confidence: 86%
“…Tumor biological factors, which constitute the tumor-node-metastasis (TNM) stage, were enacted by the American Joint Committee on Cancer (AJCC) and have been validated as indicators to evaluate CRC prognosis before patients undergo treatment [4]. However, the current TNM stage system for CRC lacks information reflecting the inflammatory status in patients.…”
Section: Introductionmentioning
confidence: 99%